Systematic definition of threatened fauna communities is critical to their conservation. Issue 3 (27th December 2018) - Fraser, Hannah; Simmonds, Jeremy S.; Kutt, Alex S.; Maron, Martine
Abstract: Aim: Most terrestrial ecological communities are defined primarily on their constituent flora. We aimed to develop a repeatable approach to defining a community, both intact and degraded, based on its fauna. We demonstrate how the approach can be used to guide conservation—for example, determining whether a multispecies community of animals is threatened. Location: Temperate and subtropical woodlands of Australia. Methods: We used expert opinion to develop a definition of the Australian Temperate and Subtropical Woodland Bird Community and metrics of its condition. Using continental‐scale vegetation change mapping, and national bird atlas data, we assessed this community against criteria for listing as a threatened ecological community under national biodiversity conservation law. Results: We defined and described a recognizable and consistent Australian Temperate and Subtropical Woodland Bird Community . Although taxonomically and functionally very similar, we identified six community variants that show species‐ or genus‐level substitutions. The community was evaluated to be Endangered or Critically Endangered across its extent based on criteria from Australia's Environment Protection and Biodiversity Conservation Act 1999 . We used a novel metric of condition using historical changes in woodland extent and bird species, to demonstrate the community has declined substantially in geographical extent and integrity and is subject to severe and ongoing threats. Conclusions: The consequences of global change affect entire communities, not just single species; however, defining ecological communities based predominantly on plant species composition can fail to illuminate the complex associations of animals that are both sustained by, and sustain, the vegetation. In this study, we present a process for defining and evaluating the status of a fauna community against threat criteria. The explicit recognition and protection of fauna communities can be an important complement to the protection of plant‐based ecological communities.